The Impact of Religious Fundamentalism on Social Development in Nigeria: A Reflection - Sibani, Cliford Meesua; Excellence, Haruna Ezekiel (NIU Journal of Social Sciences; Vol 8 No 1 (2022): NIU Journal of Social Sciences, Vol. 8 No. 1, March 2022DO - 10.58709/niujss.v8i1.1409, 2022)
Religious fundamentalism is seen as the strict observance of basic important rules and belief with unrestricted commitment by religious extremists. Social development refers the development of social skills and emotional maturity, Social development is about putting people at the centre of development. The defective religious foundation characterized by intolerance, fanaticism and lack of love has led to a number of problems in our society. Bloodshed motivated and masterminded by religious confusion has marred our beloved country for several decades. This is the logical result of the flawed concept and use of religion; the elite use religion for the exclusive purpose of perpetuating domination of the majority. They take advantage of the confusion arising from the issue of the secular nature of the Nigerian state. This paper addressed the brief history of religious fundamentalism in relation to social development in Nigeria, positive and negative fundamentalism in Nigeria, causes of religious fundamentalism in Nigeria, consequences of religious fundamentalism and religious remedies to religious fundamentalism in relation to social development in Nigeria. Historical method was used and books and journals were consulted. This research recommends that all the basic necessities of life be provided by the government as well as employment to enhance ceasefire by extremist- religious fundamentalist.